2020
DOI: 10.3389/fphar.2020.00372
|View full text |Cite
|
Sign up to set email alerts
|

A GLP-1 Analog Liraglutide Reduces Intimal Hyperplasia After Coronary Stent Implantation via Regulation of Glycemic Variability and NLRP3 Inflammasome/IL-10 Signaling in Diabetic Swine

Abstract: Objective: This study aimed to explore whether treatment with the glucagon-like peptide-1 (GLP-1) analog liraglutide reduces intimal hyperplasia after coronary stent implantation via regulation of glycemic variability, the NLRP3 inflammasome, and IL-10 in diabetic swine. Methods: Fifteen pigs were divided into a diabetes mellitus (DM) group (n = 6), a DM + liraglutide treatment group (L group) (n = 6) and a sham group (n = 3). A total of 24 everolimus-eluting stents were implanted in the left anterior descendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…In recent years, increased attention has been given to the role of aerobic glycolysis in atherosclerosis, especially the promotion of atherosclerosis occurrence and development by diabetes 15,16 . Our team's recent human clinical, animal, and cell studies showed that aerobic glycolysis‐related metabolic inflammation plays an important role in diabetes‐induced atherosclerosis 2,17 . However, the regulatory mechanism of glycolysis is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, increased attention has been given to the role of aerobic glycolysis in atherosclerosis, especially the promotion of atherosclerosis occurrence and development by diabetes 15,16 . Our team's recent human clinical, animal, and cell studies showed that aerobic glycolysis‐related metabolic inflammation plays an important role in diabetes‐induced atherosclerosis 2,17 . However, the regulatory mechanism of glycolysis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Our team's recent human clinical, animal, and cell studies showed that aerobic glycolysis-related metabolic inflammation plays an important role in diabetes-induced atherosclerosis. 2,17 However, the regulatory mechanism of glycolysis is not clear. Our study further confirmed the role of Warburg effect-related inflammation on the complexity of coronary atherosclerosis.…”
Section: Oct and Histological Analysismentioning
confidence: 99%
“…Cells were incubated with serum-free media for 24 h prior to each experiment and seeded at 1 × 10 6 cells/dish in 100 mm culture dishes for western blotting and 3 × 10 4 cells/well in 24-well-culture plates for immunofluorescence. To study the role of GLP-1R in microglial inflammation, BV-2 cells were preincubated with the selective GLP-1R agonist liraglutide (100 nM, Selleck, TX, USA) and the antagonist exendin(9-39) (200 nM, MCE, USA) for 24 h, followed by LPS (1 µg/ml, Sigma-Aldrich, MO, USA) stimulation for 24 h. The doses of these drugs used with cells were based on previous data [34][35][36].…”
Section: Body Weight and Blood Glucose Testmentioning
confidence: 99%
“…В ходе выполнения экспериментального исследования на животных с индуцированным стрептозотоцином СД оценивали эффективность применения арГПП-1 лираглутида по сравнению с контролем по влиянию на гиперплазию интимы коронарных артерий после имплантации стента за счет регуляции вариабельности уровня глюкозы в крови, а также за счет влияния на уровень инфламмасома NLRP3, который участвует в активации каспаз 1-го и 5-го типов, и соответственно, в образовании интерлейкина-1β и интерлейкина-18, т. е. цитокинов, регулирующих уровень воспаления в сосудистой стенке [34]. Кроме того, оценивали влияние применения лираглутида на концентрацию противовоспалительного цитокина интерлейкина-10 в крови.…”
Section: данные о влиянии применения аргпп-1 на коронарные артерии после их стентированияunclassified